Mutation of NLRC4 causes a syndrome of enterocolitis and autoinflammation - Romberg, Neil (2014)
Upon detection of pathogen-associated molecular patterns, innate immune receptors initiate inflammatory responses. These receptors include cytoplasmic NOD-like receptors (NLRs), whose stimulation recruits and proteolytically activates caspase-1 within the inflammasome, a multi-protein complex. Caspase-1 mediates the production of interleukin-1 family cytokines (IL1FCs), leading to fever, and inflammatory cell death (pyroptosis)(1,2). Mutations that constitutively activate these pathways underlie several autoinflammatory diseases with diverse clinical features(3). We describe a family with a previously unreported syndrome featuring neonatal-onset enterocolitis, periodic fever, and fatal/near-fatal episodes of autoinflammation caused by a de novo gain-of-function mutation (p.V341A) in the HD1 domain of NLRC4 that co-segregates with disease. Mutant NLRC4 causes constitutive Interleukin-1 family cytokine production and macrophage cell death. Infected patient macrophages are polarized toward pyroptosis and exhibit abnormal staining for inflammasome components. These findings describe and reveal the cause of a life-threatening but treatable autoinflammatory disease that underscores the divergent roles of the NLRC4 inflammasome.